Keratin-hydrotalcites hybrid films for drug delivery applications. (August 2018) - Posati, Tamara; Giuri, Demetra; Nocchetti, Morena; Sagnella, Anna; Gariboldi, Marzia; Ferroni, Claudia; Sotgiu, Giovanna; Varchi, Greta; Zamboni, Roberto; Aluigi, Annalisa
Graphical abstract: Highlights: Hybrid films made of keratin and diclofenac loaded hydrotalcytes have been developed. Compared to pure keratin films, the hybrid ones showed less swelling ratio and degradation rate. Compared to pure keratin films, the hybrid ones showed greater thermal stability. The diclofenac release from the hybrid films is faster than that from pure keratin film. Keratin/hydrotalcyte hybrid films were able to support fibroblast cells adhesion and growth. Abstract: In this work novel hybrid materials for drug delivery purposes are obtained by combining keratin with hydrotalcite nanoparticles containing diclofenac. The hybrid films showed a less pronounced swelling, porosity and degradation and a greater thermal stability compared to pure keratin films containing free diclofenac. These results, together with the slight shift towards smaller wavelength numbers of amide I band led to the hypothesis of a probable cross-linking between hydrotalcites and the protein mediated by glutaraldehyde, which results in a total reinforcing action on the hybrid material. In addition, diclofenac release profiles of the hybrid film in physiological conditions were higher than those of the non-hybrid compound. Furthermore, keratin/hydrotalcite were able to support fibroblast cells adhesion and growth suggesting their potential use as drug delivery systems for wound healing and tissue engineering applications.